Fresno County Bar Association Luncheon with State Senator Kenneth Maddy Keynote Speaker - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Hebert Levy, State Senator Kenneth Maddy, Fresno County Bar Association President-Elect G. Dana French